Comparison of arousal and preference assessment outcomes for sex offenders with intellectual disabilities. Issue 1 (20th October 2016) - Reyes, Jorge R.; Vollmer, Timothy R.; Hall, Astrid
Abstract : We compared outcomes of arousal and preference assessments for five adult male alleged sexual offenders with intellectual disabilities. Arousal assessments involved the use of the penile plethysmograph to measure changes in penile circumference to both deviant (males and females under the age of 18) and nondeviant (males and females over the age of 18) video clips. Paired‐stimulus preference assessments were arranged to present still images from the video clips used in the arousal assessments. Results showed correspondence between the assessments for four out of the five participants. Implications are discussed for the use of preference assessment methodology as a less intrusive assessment approach for sexual offender assessments.